2011
DOI: 10.1089/jwh.2010.2530
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Screening Practices Among Physicians in the National Breast and Cervical Cancer Early Detection Program

Abstract: Background: The National Breast and Cervical Cancer Early Detection Program (NBCCEDP) provides lowincome, uninsured women with screening and diagnostic services for breast and cervical cancer. Our study was conducted to describe the demographic and practice characteristics of participating and nonparticipating physicians, as well as their beliefs, adoption of new screening technologies, and recommendations for breast and cervical cancer screening. Methods: From a 2006-2007 nationally representative survey, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
10
0
4
Order By: Relevance
“…Benard et al [14] found that providers were following women in the NBCCEDP with low-grade abnormalities according to national guidelines for the study period. Additionally, national provider surveys have found that providers serving women in the NBCCEDP had similar results on screening and management beliefs and practices compared to providers who do not serve women in the NBCCEDP [15]. …”
Section: Resultsmentioning
confidence: 99%
“…Benard et al [14] found that providers were following women in the NBCCEDP with low-grade abnormalities according to national guidelines for the study period. Additionally, national provider surveys have found that providers serving women in the NBCCEDP had similar results on screening and management beliefs and practices compared to providers who do not serve women in the NBCCEDP [15]. …”
Section: Resultsmentioning
confidence: 99%
“…Awareness of VIA was considerably lower in NBCCEDPfunded jurisdictions, and few believed it was an acceptable screening method. In general, NBCCEDP policies on cervical cancer screening generally follow U.S. Preventive Services Task Force guidelines, which do not address use of VIA [4,31]. In LMICs, using primary HPV screening rather than cytology presents numerous advantages and is a feasible strategy [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The provider survey was developed specifically for this study, and is based upon national primary care provider surveys [16,17]. The survey was pilot tested with seven primary care providers in the Atlanta, GA area to estimate respondent burden, format, appropriateness and relevance of survey questions.…”
Section: Methodsmentioning
confidence: 99%